2009
DOI: 10.1016/j.jneuroling.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

“L” is for tiger: Effects of phonological (mis)cueing on picture naming in semantic aphasia

Abstract: a b s t r a c tSemantic aphasia (SA) refers to a subset of aphasic patients who exhibit multimodal semantic deficits (Jefferies, E., & Lambon Ralph, M. (2006). Semantic impairment in stroke aphasia vs semantic dementia: a case-series comparison. Brain, 129(8), 2132-2147). Consistent with their underlying semantic control deficit, SA picture naming accuracy can be improved considerably with a correct phonological cue. The performance of normal individuals in the tempo picture naming paradigm reveals an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 40 publications
9
44
2
Order By: Relevance
“…IRQ [33]; AZ [32]; 9/10 pre-and 7/8 postsurgery glioma patients [24] c spoken-to-written word matching AZ [18,25,26,32,35]; MED [16]; IRQ [33]; FBI, NBC [36] naming pairs of pictures 2/2 semantic short-term memory deficit patients [37]; JHM [38] miscueing effects in picture naming 3/3 aphasic patients [39]; 5/6 SA patients [40] a ; seven SA patients [41,42] a,e matching non-verbal sounds to pictures or words AZ, BBB [30] selecting an object to complete a common task In addition to generally inconsistent performance, individuals with access deficits exhibit declining performance over repeated presentations of a stimulus, typically called a negative serial position effect (where 'serial position' refers to repetition of the same item, unlike in serial order recall tasks where it refers to position of different items). In the simplest studies, trials were presented in a ( pseudo-)random order and repeated multiple times.…”
Section: (C) Performance Inconsistencymentioning
confidence: 99%
See 1 more Smart Citation
“…IRQ [33]; AZ [32]; 9/10 pre-and 7/8 postsurgery glioma patients [24] c spoken-to-written word matching AZ [18,25,26,32,35]; MED [16]; IRQ [33]; FBI, NBC [36] naming pairs of pictures 2/2 semantic short-term memory deficit patients [37]; JHM [38] miscueing effects in picture naming 3/3 aphasic patients [39]; 5/6 SA patients [40] a ; seven SA patients [41,42] a,e matching non-verbal sounds to pictures or words AZ, BBB [30] selecting an object to complete a common task In addition to generally inconsistent performance, individuals with access deficits exhibit declining performance over repeated presentations of a stimulus, typically called a negative serial position effect (where 'serial position' refers to repetition of the same item, unlike in serial order recall tasks where it refers to position of different items). In the simplest studies, trials were presented in a ( pseudo-)random order and repeated multiple times.…”
Section: (C) Performance Inconsistencymentioning
confidence: 99%
“…Misleading phonemic cues (e.g. the initial phoneme of a semantically related item, also called a 'miscue'), which presumably strengthen activation of semantic competitors, also lead to significantly poorer picture-naming performance in access deficit patients [39][40][41][42]. These effects have also been found in non-verbal matching tasks: non-verbal sound-to-picture (and sound-to-word) matching [30], selecting an object to complete a common task (e.g.…”
Section: (C) Performance Inconsistencymentioning
confidence: 99%
“…(2) They are highly sensitive to manipulations of the executive demands of semantic tasks-both when making judgments about word meaning (Noonan et al, 2010) and in the highly nonverbal domain of object use Corbett, Jefferies, Ehsan, et al, 2009). (3) They show strong effects of cues and task constraints that reduce the requirement for internally generated semantic control (Corbett et al, 2011;Noonan et al, 2010;Soni et al, 2009). When naming pictures, SA performance is substantially improved by phonological cues, although SD patients only show a modest benefit ( Jefferies, Patterson, & Lambon Ralph, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When naming pictures, SA performance is substantially improved by phonological cues, although SD patients only show a modest benefit ( Jefferies, Patterson, & Lambon Ralph, 2008). SA patients are also sensitive to semantic miscues (e.g., /d/ when attempting to name "cat"; Noonan et al, 2010;Soni et al, 2009). Moreover, they show parallel effects of task constraints in object use .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Noonan et al, 2010;Soni et al, 2009) has shown that category co-ordinate cues interfere with SA patients' naming. In Soni et al (2009), a significant overall cueing effect on accuracy was seen between co-ordinate miscues and correct cues and the negative cueing effect between miscues and neutral cues was marginally significant. This cueing effect was driven by differences in semantic error rates, showing that the cues were acting at the level of semantics in these patients; as in accuracy, the overall cueing effect on semantic errors was significant.…”
Section: Introductionmentioning
confidence: 95%